Design and development of sulfenylated 5-aminopyrazoles as inhibitors of acetylcholinesterase and butyrylcholinesterase: exploring the implication for Aβ1-42 aggregation inhibition in Alzheimer's disease - Rani P.; Chahal S.; Ranolia A.; Kiran; Kumar D.; Kataria R.; Kumar P.; Singh D.; Duhan A.; Jha V.; Wahajuddin M.; Joshi G.; Sindhu J. (My University, 2025)
Current therapeutic regimens approved to treat Alzheimer's disease (AD) provide symptomatic relief by replenishing the acetylcholine levels in the brain by inhibiting AChE. However, these drugs don't halt or slow down the progression of Alzheimer's disease, which remains a major challenge. Evidence suggests a significant increase in BuChE activity with a decrease in AChE activity as the AD progresses along with the Aβ1-42 aggregation. To address this unmet need, we rationally developed sulfenylated 5-aminopyrazoles (3a-3o) via electro-organic synthesis in good to excellent yields (68-89%) and duly characterized them using spectrophotometric techniques. The compounds were tested for acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) inhibition, with 3b (4-NO2) showing the highest potency. It exhibited IC50 values of 1.634 ± 0.066 μM against AChE and 0.0285 ± 0.019 μM against BuChE, outperforming donepezil and tacrine. Admittedly, 3b effectively inhibited Aβ1-42 aggregation and enhanced working memory, as indicated by the Y-maze test, besides portraying no cytotoxicity. The outcome was further corroborated using in silico techniques, leading to the elucidation of plausible inhibition and metabolism mechanisms. © 2025 RSC.